Relasi kuasa dalam pengembangan perangkat lunak open source perpustakaan perguruan tinggi di Bali - I Putu Suhartika; Ni Putu Premierita Haryanti (Perpustakaan Universitas Gadjah Mada, 2021)
Introductions. Discussions on critical perspectives of open source software is limited as most studies focus on technical aspects. This study examines aspects of process, form, ideology, and implications of power relations in the development of open source software for university libraries in Bali, observed from non-technical aspects of the system. Research methods. The paper used cultural studies method with semi-structured interviews, observation, and documentation as data collection methods. Data analysis. This study used genealogy and deconstruction methods involving Foucault and Derrida theory. Results and discussion. The process of power relations in the development of open source software for university libraries in Bali is not only comes in parallel, but also in hegemonic relations. These relations are based on knowledge and influenced by the ideology of librarianship, free, open source, and capitalist which have implications for libraries, librarians, and users. Conclusions and suggestions. The practice of power relations in the development of open source software for university libraries in Bali occurred through knowledge and hegemonic power. Therefore, human resources should also improve their communication skills.